Sintering and Mechanical Properties of Injection Molded Low Cost Ti Alloys - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2013)
This study focuses on the injection molding of Ti-Fe alloys. Low cost Ti alloy (Ti-Fe) was manufactured following a powder injection molding route. The Ti and Fe powders were dry mixed and molded with wax based binder. Binder debinding was performed by solvent and thermal method. After dedinding, the samples were sintered at 1100 degrees C and 1300 degrees C for 1 h in vacuum. Metallographic studies were conducted to extend densification and the corresponding microstructural changes. The sintered samples were characterized by measuring tensile strength, elongation and hardness. All powder, fracture surfaces of molded and sintered samples were examined using scanning electron microscope. The sintered density, tensile strength and hardness of injection molded Ti-Fe samples increases with increasing sintering temperature.
Keywords: Titanium alloy; Powder injection molding; Sintering; POWDER